The effect of social media marketing on the growth of business: evidence from selected Small and Medium Enterprises (SMEs) in Benin City, Nigeria - Eleazar Chibuzor Gbandi; Gloria Osasere Iyamu (Journal of Enterprise and Development (JED), 2022)
Purpose — This research investigated the effect of social media marketing on small and medium-sized business growth in Benin City, Nigeria.Research method — The study adopted a cross-sectional research design and data was gathered using a specially prepared questionnaire which was scored on a 5-point Likert scale. Four aspects of social media marketing were chosen to be studied: Facebook, Instagram, Twitter, and YouTube. The population of the study includes all SMEs in Benin City, Nigeria. The study's sample size was 500 selected SMEs. The acquired data were analysed using descriptive and inferential statistics.Result — Facebook, Instagram, Twitter, and YouTube were all found to have a positive and significant impact on the growth of SMEs.Recommendation — Based on the findings of the study, we urge that SMEs be encouraged to embrace social media marketing in order to compete in the global market. SME owners should also keep their social media accounts updated with content that educates, informs, and persuades customers to buy their products. In addition, SMEs owners should use social media marketing feedback as a catalyst for innovation and expansion.